2017
DOI: 10.1088/1361-6587/aa90ee
|View full text |Cite
|
Sign up to set email alerts
|

The effects of electron cyclotron heating and current drive on toroidal Alfvén eigenmodes in tokamak plasmas

Abstract: View the article online for updates and enhancements. Recent citations Kinetic equilibrium reconstruction for the NBI-and ICRH-heated H-mode plasma on EAST tokamak Zhen ZHENG et al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…Studies have been made on the physical properties of specific modes, and several external actuators have been proposed and demonstrated in tokamaks and helical devices for controlling and/or stabilizing EP-driven modes [4]. Promising control techniques are based on (i) varying the energetic-ion sources to modify the gradients in the energetic ion-distribution [5][6][7][8][9][10], (ii) localized electron cyclotron heating (ECH) to modify the energetic-ion slowing-down distribution [11][12][13][14][15][16][17][18], (iii) a localized electron cyclotron current drive (ECCD) for modifying the equilibrium [19,20] and (iv) externally applied 3D perturbative magnetic fields for manipulating the energetic-ion distribution and thus the wave drive [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been made on the physical properties of specific modes, and several external actuators have been proposed and demonstrated in tokamaks and helical devices for controlling and/or stabilizing EP-driven modes [4]. Promising control techniques are based on (i) varying the energetic-ion sources to modify the gradients in the energetic ion-distribution [5][6][7][8][9][10], (ii) localized electron cyclotron heating (ECH) to modify the energetic-ion slowing-down distribution [11][12][13][14][15][16][17][18], (iii) a localized electron cyclotron current drive (ECCD) for modifying the equilibrium [19,20] and (iv) externally applied 3D perturbative magnetic fields for manipulating the energetic-ion distribution and thus the wave drive [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The non inductive current drive is a promising mechanism to achieve steady state operation in advanced tokamaks where large bootstrap currents replace the magnetic field component generated by the transformer coils [10,11,12]. In addition, the non inductive current drive is used to modify the magnetic field configuration of the fusion devices, for example by the electron cyclotron current drive (ECCD) [13,14] and the neutral beam current drive (NBCD) [15,16,17,18], leading to an improved stability of the pressure and current gradient driven modes (PM) [19,20,21,22,23,24] as well as the Alfvén Eigenmodes (AE) [25,26]. ECCD is also used in stellarators [27,28,29,30] to improve the stability properties of the plasma with respect to the PM and AE [31,32,33,34,35,36,37,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical investigations [61,72,73] of the plasma pressure gradient effect upon the TAE stability have shown that the core localized TAEs can be suppressed when the normalized pressure gradient (α) exceeds a critical level (α c ) as described in equations ( 1) and ( 2), considering finite aspect ratio at finite beta [24][25][26]:…”
Section: Damping Effectmentioning
confidence: 99%
“…The correlation between performance degradation and AE activities has been investigated widely. At present-day experiments, various AE control tools such as electron-cyclotron (EC) waves, external magnetic perturbations and fast-ion pressure gradient change have been investigated and tested in tokamaks [20][21][22][23][24][25][26] and helical devices [27][28][29][30]. Among the various control tools, the electron cyclotron current drive (ECCD) is one of the most promising techniques because a flexible deposition of the EC waves is possible on the location where the AEs are excited.…”
Section: Introductionmentioning
confidence: 99%